Caractérisation Physico-Chimique Et Étude De La Toxicité De La Lagune Côtière, De Togbin À GrandPopo (Sud-Ouest Bénin) - Chouti, Waris Kéwouyèmi; Chitou, Nafiou Egbéola; Kelome, Nelly; Kpako, Boris Boniface H.; Vlavonou, Dorcas Honvou; Tossou, Michael (European Scientific Journal, ESJ, 2017)
This work deals with the physicochemical characterization and the toxicity study of the coastal lagoon of Benin (from Togbin to Grand-Popo). In particular, it has to do with the study of copper and zinc. The sampling campaign was carried out by motorized boat on the 20th of December 2016. Samples were taken a few centimeters below the surface of the water. The analysis of the metals was carried out with a HACH LANGE DR2800 spectrophotometer. Copper is determined by the method of Bicinchroninate, while zinc is determined by the method of Zincover. The method used for the toxicity study is natural and is based on the inoculation of onions in the waters sampled at various proportions. The results revealed that physically and chemically, the lagoon is highly mineralized. This mineralization is due not only to the contribution of the sea to high tide, but also to salt production in Djègbadji. Concerning the concentrations of trace metallic elements, copper and zinc do not pose a risk to humans, but pose a high risk to the aquatic organisms present in the lagoon. Potentially suspected sources of copper and zinc are Ahémé Lake and the Mono River. As for the ecotoxicological study with the Allium cepa test, this test is not only influenced by metals, but also by the salinity of the water. The test revealed that the waters of the lagoon are acutely toxic, particularly at Djondji. Strategies for the protection and rehabilitation of the coastal lagoon must be undertaken by decision-makers at all levels. This, therefore, will help to prevent not only the different populations from the risks of diseases, but also increase the economy of the country through marketing and the edibility of the fish and even offer a framework of tourist scale.